2015
DOI: 10.31729/jnma.2770
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Iron Sucrose Therapy in Iron Deficiency Anemia in Antenatal and Postnatal Patients

Abstract: Introduction: Iron deficiency anemia is the most common nutritional deficiency in pregnancy and more common in developing countries which is aggravated due to increased demand and blood loss during delivery. Though there are different methods for treating iron deficiency anemia. Iron sucrose is being used because of its minimal side effects. This study was undertaken to evaluate the response and effect of intravenous iron sucrose given to patient in antenatal and postnatal period with moderate iron deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Of note, 6 studies were RCTs, 21 , 22 , 23 , 24 , 25 , 26 and 6 more were nonrandomized controlled, that is, cluster-controlled 27 , 28 , 29 , 30 or were before and after studies. 31 , 32 In addition, 9 were cohort studies, 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 2 were cross-sectional, 42 , 43 1 was a pure qualitative study 44 , and another had cluster-controlled and qualitative elements. 45 Notably, 15 of the studies involved community-based interventions, 22 , 23 , 26 , 27 , 28 , 29 , 31 , 34 , 36 , 37 , 38 , 39 , 40 , 44 , 45 9 were hospital-based, 21 , 24 , 25 , 30 , 32 , 33 , 35 , 42 , 43 , and 1 contained elements of both.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of note, 6 studies were RCTs, 21 , 22 , 23 , 24 , 25 , 26 and 6 more were nonrandomized controlled, that is, cluster-controlled 27 , 28 , 29 , 30 or were before and after studies. 31 , 32 In addition, 9 were cohort studies, 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 2 were cross-sectional, 42 , 43 1 was a pure qualitative study 44 , and another had cluster-controlled and qualitative elements. 45 Notably, 15 of the studies involved community-based interventions, 22 , 23 , 26 , 27 , 28 , 29 , 31 , 34 , 36 , 37 , 38 , 39 , 40 , 44 , 45 9 were hospital-based, 21 , 24 , 25 , 30 , 32 , 33 , 35 , 42 , 43 , and 1 contained elements of both.…”
Section: Resultsmentioning
confidence: 99%
“…31 , 32 In addition, 9 were cohort studies, 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 2 were cross-sectional, 42 , 43 1 was a pure qualitative study 44 , and another had cluster-controlled and qualitative elements. 45 Notably, 15 of the studies involved community-based interventions, 22 , 23 , 26 , 27 , 28 , 29 , 31 , 34 , 36 , 37 , 38 , 39 , 40 , 44 , 45 9 were hospital-based, 21 , 24 , 25 , 30 , 32 , 33 , 35 , 42 , 43 , and 1 contained elements of both. 41 The detailed summaries of the included studies can be found in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations